(Dis)Continuity: The cultural intelligence hypothesis reconsidered. (May 2018) - Kuhle, Anneliese
Abstract: According to linguistic functionalism, the cultural theory of language rests on the assumption of general learning abilities in the human individual. Such general intelligence encompasses various capabilities, including an efficient working memory, swift learning from experience, and the ability to plan complex actions under displaced conditions. Over the past two decades, a further hypothesis has emerged that social intelligence, in particular, explains the human-unique ability to engage in linguistic behavior. In this view, humans possess a special predisposition for social cooperation, along with an ability to understand others, not grounded in general intelligence. This trend has produced an unfortunate effect, namely, that the cultural theory of language no longer invokes cognitive continuity, i.e., homology—a critical point originally used to defend functionalism against generative theorizing. The current paper draws attention to this problem and critically analyzes the premises of the social intelligence hypothesis in its opposition to the notion of general intelligence. It concludes that linguistic explanations embracing functionalism are more compatible with claims of continuity in that they can acknowledge, rather than deny, the cultural abilities of nonhuman primates. Highlights: Current research in evolutionary psychology and linguistics argues in favor of a social intelligence hypothesis. The general intelligence hypothesis assumes a significant continuity between the human cultural capacity and nonhuman cultural abilities. The social intelligence hypothesis assumes a major discontinuity and argues in favor of human-unique, socio-cognitive skills. Linguistic functionalism currently prefers the conception of language as a social phenomenon. The conception of language as a tool of communication, on the other hand, rests on the notion of general intelligence and supports cognitive homology.